2016
DOI: 10.5194/hess-2016-63
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time monitoring of nitrate transport in deep vadose zone under a crop field – implications for groundwater protection

Abstract: Abstract. Nitrate is considered the most common non-point pollutant in groundwater. It is often attributed to agricultural management, when excess application of nitrogen fertilizer leaches below the root zone and is eventually transported as nitrate through the unsaturated zone to the water table. A lag time of years to decades between processes occurring in the root zone and their final imprint on groundwater quality prevents proper decision-making on land use and groundwater-resource management. In this stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Accordingly, variations in the chemical characteristics of the soil porewater may be detected continuously at the same spot in the subsurface over many years. A detailed description of the VMSs at each site can be found in Dahan et al 120 (2014) and Turkeltaub et al (2014Turkeltaub et al ( , 2015Turkeltaub et al ( , 2016, and in section S1. Additional information on the research site locations, crop types, and irrigation and fertilization regimes can be found in section S2.…”
Section: Selected Agricultural Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, variations in the chemical characteristics of the soil porewater may be detected continuously at the same spot in the subsurface over many years. A detailed description of the VMSs at each site can be found in Dahan et al 120 (2014) and Turkeltaub et al (2014Turkeltaub et al ( , 2015Turkeltaub et al ( , 2016, and in section S1. Additional information on the research site locations, crop types, and irrigation and fertilization regimes can be found in section S2.…”
Section: Selected Agricultural Sitesmentioning
confidence: 99%
“…The porewater samples were obtained from each site by the VMS from 6-8 sampling points distributed vertically 180 and laterally under each site (S3). Note that the VMS sampling ports are permanently installed at the site and therefore enable repeat sampling from the exact locations for many years, while the agricultural activity on land surface remains undisturbed (Turkeltaub et al, 2015(Turkeltaub et al, , 2016.…”
Section: Uv Absorption Characteristics Of Agricultural Soil Porewatermentioning
confidence: 99%
“…One site practice organic regime that is based on the application of organic compost as the main fertilizer, while the other applied conventional fertigation methods. Detailed Description of the VMS at each site was previously presented at Dahan et al, (2014); Turkeltaub et al, (2014Turkeltaub et al, ( , 2015aTurkeltaub et al, ( , 2016.…”
Section: Section -S2 Selected Agricultural Sitesmentioning
confidence: 99%
“…Leaching of N applied to agricultural land below the effective root zone is of great concern to groundwater quality worldwide (Green et al, 2008; Hallberg, 1987; Huang et al, 2011; Viers et al, 2012). However, large spatial and temporal variability in leachable N concentrations (mainly nitrate N [NO 3 − –N]) below the effective root zone, at the scale of typical field vadose zone instrumentation, makes it difficult to accurately quantify NO 3 − losses to groundwater (Baram et al, 2016; Kurtzman et al, 2013; Onsoy et al, 2005; Turkeltaub et al, 2016). In view of emerging regulatory programs in Europe (Drevno, 2016; Tsakiris, 2015), California (Dowd et al, 2008; Harter et al, 2005), and elsewhere, there is considerable interest in the assessment and the development of methods that would enable more accurate estimates of NO 3 − losses from agricultural fields to groundwater.…”
mentioning
confidence: 99%
“…In some, mass balance along with in situ pore water sampling from below the effective root zone was used to evaluate NO 3 − losses under different N management practices (Li et al, 2007). In others, point measurements of changes in water content and NO 3 − concentrations across the entire vertical domain of a deep (>15 m) vadose zone were used to calibrate flow and transport models (Turkeltaub et al, 2016, 2015). However, such studies fail to address the large degree of spatial horizontal and vertical variability in NO 3 − distribution, fate, and transport below the root zone at the field or orchard scale (>0.10 km 2 ) (Baram et al, 2016; Botros et al, 2012; Onsoy et al, 2005).…”
mentioning
confidence: 99%